'Like snow in a dark night': Exile and displacement in the poetics of Robert Graves. Issue 1 (1st September 2018) - Joseph, Michael
Behind the redoubtable self-confidence of a poet who Randall Jarrell famously declared, 'could explain anything', and characterized bad poetry as 'yours, when I do not like it or understand it', Robert Graves was profoundly divided. One can trace that division in his self-exile from England in 1929 and the manner in which he thereafter arranged his life between Mallorca and England. His memoir, Good-Bye to All That, features only one side of his nature – the desire to turn his back on modernity and all it symbolized, and to immerse himself in the ahistorical world of the Goddess – but there was another side as well: deterministically modern, civilized, historical, ironic, English. In 'Like Snow in a Dark Night', I discuss this fundamental yet understudied split in Graves's character in terms of its metaphorical presence in his poetry, in which images of exile, displacement, liminality, indeterminacy and elusiveness appear to evoke and celebrate a condition of being both here and there, and neither here nor there, as the essential condition for inspiration.